The effects of soft drinks on the released of calcium from the enamel surface - Miranti, Diandra Audyla; Sukartini, Endang; Andang, Milly Armilia (Universitas Padjadjaran, 2015)
Introduction: Calcium release from the enamel surface is known as enamel demineralisation. Enamel demineralisation is a chemical process of mineral loss from the email structure. One of the factors that cause demineralisation is the presence of acids derived from food or beverages consumed. This study was aimed to determine the effects of soft drinks and the amount of calcium release from the enamel surface. Methods: This study was an in-vitro experimental. The population was extracted maxillary premolars from orthodontics clinics in health centres, hospitals, and private clinics throughout Bandung and Jakarta. As many as 20 crown of maxillary premolars divided into two groups. Dissolved calcium was measured using the Atomic Absorption Spectrophotometry (AAS). Data obtained was tested using an independent t-test. Results: The results showed that the amount of calcium released after exposure of soft drink was higher than soda water. The average amount of calcium released after soft drink exposure was 4122 ppm and soda water was 3492 ppm. Conclusion: Soft drink affects the calcium release from the enamel surface.